2018
DOI: 10.1111/anae.14222
|View full text |Cite
|
Sign up to set email alerts
|

A triple‐blind, placebo‐controlled randomised trial of the ilioinguinal‐transversus abdominis plane (I‐TAP) nerve block for elective caesarean section

Abstract: This study investigated the efficacy of a new ilioinguinal-transversus abdominis plane block when used as a component of multimodal analgesia. We conducted a prospective, triple-blind, placebo-controlled randomised study of 100 women undergoing elective caesarean section. All women had spinal anaesthesia with hyperbaric bupivacaine, 15 μg fentanyl and 150 μg morphine, as well as 100 mg diclofenac and 1.5 g paracetamol rectally. Women were randomly allocated to receive the ilioinguinal-transversus abdominis pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
0
20
0
3
Order By: Relevance
“…It also reduced pain scores at rest and with movement in the first 24 hours postoperatively 48. There was no difference in sedation, nausea, vomiting, or pruritus between the groups; however, there was one report of a femoral nerve palsy after II-IH nerve blockade 48. While more evidence is needed before IH-II blocks can be recommended as a reliable technique for cesarean delivery analgesia, the availability of other peripheral blocks with a greater degree of dermatomal spread (and potential visceral effect) suggests that research time and effort are better spent in other areas.…”
Section: Ilioinguinal-iliohypogastric Blockmentioning
confidence: 86%
See 3 more Smart Citations
“…It also reduced pain scores at rest and with movement in the first 24 hours postoperatively 48. There was no difference in sedation, nausea, vomiting, or pruritus between the groups; however, there was one report of a femoral nerve palsy after II-IH nerve blockade 48. While more evidence is needed before IH-II blocks can be recommended as a reliable technique for cesarean delivery analgesia, the availability of other peripheral blocks with a greater degree of dermatomal spread (and potential visceral effect) suggests that research time and effort are better spent in other areas.…”
Section: Ilioinguinal-iliohypogastric Blockmentioning
confidence: 86%
“…In a prospective, triple-blind, placebo-controlled randomized trial, the combined I-TAP demonstrated reduced opioid use compared with placebo at all time points. It also reduced pain scores at rest and with movement in the first 24 hours postoperatively 48. There was no difference in sedation, nausea, vomiting, or pruritus between the groups; however, there was one report of a femoral nerve palsy after II-IH nerve blockade 48.…”
Section: Ilioinguinal-iliohypogastric Blockmentioning
confidence: 97%
See 2 more Smart Citations
“…53 Several other abdominal wall blocks have also been proposed for cesarean delivery, including the transverse abdominis plane blocks, 54 erector spinae plane block, 55,56 and the iliohypogastric and ilioinguinal nerve blocks. 57,58 However, multimodal analgesia inclusive of spinal PAIN MEDICINE morphine is a strong analgesic that may mitigate the need for any additional interventions. Indeed, this has been previously demonstrated for transversus abdominis plane block, which, when used as a part of a multimodal regimen inclusive of spinal morphine, does not add any analgesic benefits.…”
Section: Discussionmentioning
confidence: 99%